Studi Laboratorium Pengaruh Penambahan Bubuk Tulang Sotong sebagai Bridging Agent pada Lumpur Pemboran - Fatma, Fatma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
During drilling operations, when the reservoir zone is penetrated, the rock formation generally has high porosity and permeability, which can cause lost circulation. To overcome this problem, a bridging agent in the form of calcium carbonate (CaCO₃) is used because it is acid soluble and can temporarily seal the formation pores. Cuttlebone is known to contain a high amount of CaCO₃, so it has potential as an alternative bridging agent. This study aims to evaluate the effectiveness of CaCO₃ derived from cuttlebone as a bridging agent in drilling fluid. The evaluation was carried out through filtration tests and observation of mud cake characteristics. The test results show a low filtrate volume of 4.8–6 mL within 30 minutes and created thin and compact mud cake with an average thickness of 0.398-0,794 mm. These results indicate that CaCO₃ from cuttlebone is effective in sealing formation pores and preventing lost circulation in the productive zone.